2020
DOI: 10.3389/fevo.2020.00028
|View full text |Cite
|
Sign up to set email alerts
|

PCR Cloning Combined With DNA Barcoding Enables Partial Identification of Fish Species in a Mixed-Species Product

Abstract: DNA barcoding is a valuable tool for regulatory identification of fish species; however, it does not perform well when multiple species are present within the same food product. Therefore, the objective of this study was to examine the use of PCR cloning to identify fish in a mixed-species product that cannot be identified with standard DNA barcoding. A total of 15 fish ball mixtures were prepared with known amounts of Nile tilapia (Oreochromis niloticus), Pacific cod (Gadus macrocephalus), and walleye pollock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In the present study, DNA barcoding was applied to investigate mislabeling in different pet food products, including canned meats, jerky, particle, and snacks. The available reports demonstrated that DNA barcoding is a promising approach for detecting fish, meat and poultry species in food products (Handy et al, 2011;Armani et al, 2015;Silva et al, 2020). Moreover, combining PCRs and cloning targeting a barcode region may be an effective method to determine species from mixed-species products (Silva et al, 2020).…”
Section: Pet Food Mislabelingmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, DNA barcoding was applied to investigate mislabeling in different pet food products, including canned meats, jerky, particle, and snacks. The available reports demonstrated that DNA barcoding is a promising approach for detecting fish, meat and poultry species in food products (Handy et al, 2011;Armani et al, 2015;Silva et al, 2020). Moreover, combining PCRs and cloning targeting a barcode region may be an effective method to determine species from mixed-species products (Silva et al, 2020).…”
Section: Pet Food Mislabelingmentioning
confidence: 99%
“…The available reports demonstrated that DNA barcoding is a promising approach for detecting fish, meat and poultry species in food products (Handy et al, 2011;Armani et al, 2015;Silva et al, 2020). Moreover, combining PCRs and cloning targeting a barcode region may be an effective method to determine species from mixed-species products (Silva et al, 2020). However, DNA degradation during food processing may restrict the recovery of barcode sequences from examined effects.…”
Section: Pet Food Mislabelingmentioning
confidence: 99%
See 2 more Smart Citations